The effects of alkali treatment on the interfacial adhesion of bamboo fibres - King Jye, Wong (Institution of Mechanical Engineers, 2010)
In the present work, the potential of using bamboo fibres as reinforcement for polyester composites was evaluated. Two types of bamboo fibres were used: untreated and treated with different NaOH concentrations (1, 3, and 5wt%). Mechanical properties of both treated and untreated fibres were investigated. In addition, single-fibre pull-out tests were performed to study the interfacial shear strength of the fibres with the polyester matrix at different embedment length of fibres. Scanning electron microscopy was used to study the surface morphology of the fibres before and after the tests. Results revealed that an untreated fibre has the best strength and stiffness but lowest strain at break. An increase in alkali concentration reduces the strain at failure and ductility of bamboo fibres. However, the strength and stiffness of the fibres were increased. In addition, the interfacial shear strength was improved with longer embedment length and higher NaOH concentration.